2019
DOI: 10.1097/mao.0000000000002254
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Allografts Compared With Autologous Tissue in Tympanoplasty

Abstract: Objective: There are no direct comparisons between the success of collagen allografts versus traditional autografts for tympanic membrane (TM) repair. We sought to compare success rates in a large series of patients undergoing tympanoplasty using collagen allografts versus autologous tissues. Study Design: Retrospective review. Setting: Academic medical center. Subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…With an analysis of 255 patients, there were no statistically significant differences in the failure rate between collagen allografts and the analysed autologous tissues. Nevertheless, even not significantly, the chances of success of cartilage and perichondrium were 7.5 times higher than of collagen allografts [22] . Particularly, acellular dermis allograft is commonly used in the field.…”
Section: Biomaterial-based Strategies To Repair Tympanic Membrane Per...mentioning
confidence: 83%
“…With an analysis of 255 patients, there were no statistically significant differences in the failure rate between collagen allografts and the analysed autologous tissues. Nevertheless, even not significantly, the chances of success of cartilage and perichondrium were 7.5 times higher than of collagen allografts [22] . Particularly, acellular dermis allograft is commonly used in the field.…”
Section: Biomaterial-based Strategies To Repair Tympanic Membrane Per...mentioning
confidence: 83%
“…A single study found perforation location to be predictive of anatomic failure. 8 The remaining studies showed that perforation location did not significantly impact anatomic 10,26,29,30,[32][33][34][35][36][37][38][39][40][41][42][43] or functional 10,29,34,44 success.…”
Section: Anterior Perforationsmentioning
confidence: 97%
“…A single study claimed that the presence of cholesteatoma predicted anatomic failure; however, a statistical analysis supporting this claim was not presented. 45 Just 2 other studies analyzed the impact of presence of cholesteatoma on anatomic success and did not find it to predict failure compared to other causes of perforation 43 or other types of chronic ear inflammation. 46 Fifteen studies provided hearing outcomes for cholesteatoma cases.…”
Section: Tympanoplasty In Cholesteatoma Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become the standard procedure for repairing a tympanic membrane (2), and represents one of the first surgical procedures an otologic surgeon learns (3). As its basic principles still remain the same since its first introduction, many publications usually explain, in the introduction, that tympanoplasty has been a successful technique since Horst Ludwig Wu ¨llstein , a German otologist in Wu ¨rzburg, and Fritz Zo ¨llner (1901Zo ¨llner ( -1986, a German Austrian-born otologist in Freiburg, first proposed it in the 1950s (4,5), or sometimes more precisely in 1952 (6). Two English publications are generally mentioned as references, the 1955 Zo ¨llner paper (7), and the 1956 Wullstein paper (8).…”
Section: Introductionmentioning
confidence: 99%